IMPLEMENTASI ETIKA DI DUNIA PENDIDIKAN (STUDI KASUS SMPN 51 MERANGIN) - Hasmailena Saragih; Evi Susanti; Hanibar; Sisca Yuliasary; Desi Khoridatul (STKIP Subang, 2026)
This study aims to analyze the implementation of ethics in education through a case study at SMPN 51 Merangin. The study used a qualitative approach with a case study type through in-depth interviews, observation, and documentation techniques. Data analysis was conducted using the Miles, Huberman, and Saldaña (2020) model which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of ethics at SMPN 51 Merangin is in the good to very good category, especially in the aspect of teacher professional ethics. Based on the data obtained, the level of teacher ethics implementation reached 86.4%, reflecting discipline, exemplary behavior, communication ethics, integrity, and compliance with the code of ethics. Meanwhile, the implementation of ethics among students showed a percentage of 73.2% with the highest achievement in the indicators of cooperation and tolerance, and the lowest achievement in the indicator of honesty. Documentation data also showed 27 student violations during one semester, dominated by lateness violations. These findings indicate that although teacher ethics are strongly reflected in daily practice, strengthening ethics in students still needs improvement, particularly in the areas of responsibility, honesty, and compliance with school rules. Overall, the implementation of ethics at SMPN 51 Merangin has been quite effective, but further strategies involving collaboration between the school, family, and the social environment are still needed to achieve optimal student character.